Depression Mechanism of Sodium Sulfide in Flotation Separation of Molybdenite and Bismuthinite. (18th August 2022) - Liu, Runqing; Zhong, Chongyi; Lin, Shangyong; He, Dongdong; Sun, Wei
ABSTRACT: Sodium sulfide has been widely used as a bismuth depressant in the flotation separation of molybdenum–bismuth sulfide ores. However, the selective depression mechanism of sodium sulfide on bismuthinite remained unclear. In this study, the effect of sodium sulfide on the flotation performance of molybdenite and bismuthinite was systemically investigated through micro-flotation tests, bench-scale flotation tests, Fourier transform infrared (FTIR) measurements, adsorption experiments, and X-ray photoelectron spectroscopy (XPS) analyses. Micro-flotation tests indicated that sodium sulfide had excellent depressing effect on the bismuthinite in alkaline condition. The recovery of bismuthinite dramatically decreased from 86.7% to 16.5% with the concentration of sodium sulfide increased to 1 × 10 −3 mol/L. By contrast, the depressing effect of sodium sulfide on the flotation of molybdenite was weak. The flotation recovery of molybdenite remained above 60% in the whole pH range tested. Surface analysis using FTIR and XPS analysis revealed that the surface of bismuthinite was covered by hydrophilic sulfide ions after treatment with sodium sulfide, which not only decreased its surface hydrophobicity but also prevented the subsequent adsorption of collector xanthate. While the surface of molybdenite was slightly affected and remained hydrophobic as indicated by high flotation recoveries. Bench-scale flotation tests confirmed that sodium sulfide could be used as an efficient depressant for flotation separation of molybdenite from bismuthinite. The work presented here not only provides a new perspective on the inhibition mechanism of sodium sulfide but also gives a theoretical support for the industrial application of sodium sulfide.